Detection and partial characterization of an inhibitor of plasminogen activator in human platelets. - Erickson, L A (1984)
In this study, we demonstrate the presence of a previously undescribed fibrinolytic inhibitor in human serum. It has an apparent molecular weight of 50,000 and is not detected in serum derived from platelet-poor plasma, suggesting that it originates from platelets. This conclusion is supported by a number of observations. For example, extracts of washed, gel-filtered human platelets contain an inhibitor of similar activity and size, and physiological concentrations of thrombin induce its release from the platelets. Moreover, the kinetics and dose dependency of this release are similar to those observed for the release of platelet factor 4, and the release of both molecules is blocked by pretreating the platelets with prostaglandin E1 and theophylline. Mixing experiments, which were devised to investigate the specificity of the inhibitor, showed that the fibrinolytic activity initiated by both urokinase and tissue-type plasminogen activator was blocked by platelet releasate in a dose-dependent manner. In both cases, the amount of inhibition increased when the releasates were preincubated with the purified activators, indicating a direct interaction between the activators and an inhibitor(s). The inhibitory activity was removed by preincubating the releasates with antiserum prepared against an antiactivator purified from cultured bovine aortic endothelial cells. These results indicate that platelets contain an inhibitor which is released by thrombin, inhibits both urokinase and tissue-type plasminogen activator, and is immunologically similar to an inhibitor produced by endothelial cells. This molecule may represent a new class of inhibitors, the antiactivators, which function together with alpha 2-antiplasmin to regulate the fibrinolytic system of the blood. Its release from platelets by thrombin may protect the growing thrombus against premature dissolution initiated by plasminogen activators released by the endothelium.